Coupled K-SVD Dictionary Learning for Single Image Super-Resolution in Wavelet Domain - Ahmed, Junaid (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2015)
This thesis introduces coupled K-Singular Value Decomposition (K-SVD) algorithm in wavelet domain for Single Image Super-Resolution (SISR). In the coupled K-SVD the best low-rank approximation given by the SVD is implemented to update the LR and HR dictionaries which in turn help to enforce the equality of the sparse representation coefficients at two resolution levels. Wavelet domain produces better results due to desirable properties such as persistence across scale, compactness, directionality and analysis in many levels with the addition of redundancy in the sparse representations. Using this approach, one can design multiple structured redundant dictionaries, which can potentially help reduce the number of dictionary atoms. Three pairs of coupled low and high resolution wavelet subband dictionaries are designed. Given the low resolution image one first estimates the sparse representation coefficients using the low resolution dictionary and then reconstructs the high resolution image using the calculated low resolution sparse coefficients and high resolution dictionary. This approach generates HR images that are competitive or even better when compared with the state of the art algorithms. Results are improved in terms of PSNR and SSIM in comparison. Keywords: Coupled K-SVD, Wavelets, Single Image Super-Resolution.

ÖZ : Bu tez tek resimlerin çözünürlügünü artırmak için dalgacik bölgesinde birleştirilmiş K-SVD algoritmasını tanıtmaktadır. Birleştirilmiş K-SVD algoritmasında en iyi düşük kerte SVD yakınlaştırması kullanılarak hem alçak hem de yüksek çözünürlükteki sözlükler değiştirilmektedir. Böylece, alçak ve yüksek çözünürlükteki seyrek temsiliyet katsayılarının eşitliği zorlanmaktadir. Dalgacık uzayının kullanımı daha iyi sonuçlar vermektedir. Bunun sebebi dalgacıkların ölçeklemeye dayanaklı olması, üç temel yöne cevap verebilmesi ve ayrıtların (edge) değişik dalgacık seviyelerinde iz bırakabilmesidir. Ayrıca, dalgacık dönüşümü tasarlanan sözlüklerde artıklık yaratmaktadır. Sözlükler dalgacıkların yapılarını taşıyacakları için daha küçük olmaları mümkün kılınmaktadır. Böylece hesaplama karmaşıklıgınım da azaltılması sağlanacaktır. Her bir dalgacık bandı için bir çift ilintili sözlük tasarlanmıştır. Çiftler alçak ise yüksek çözünürelükteki sözlüklerden öluşmaktadir. Verilen bir alçak çözünürelükteki sözlüklerden öluşmaktadir. Verilen bir alçakç özünürelükteki resim önce yamalarına ayrılmakta ve her yama için alçak çözünürelükteki sözlük kullanılarak seyrek temsiliyet katsayıları hesaplanır. Yüksek çözünürelükteki seyrek temsiliyet katsayılarının aynı olduğn varsayımı ile yüksek çözünürelükteki ilintili sözlük kullanılmak suretiyle yüksek çözünürlük yamaları hesaplanmaktadır. Yamalardan örtüştürerek toplama yöntemi ile yüksek çözünürlük resmini oluşturmaktadır. Bu yaklasım ile elde edilen sonuçlar literatürdeki en iyi algoritmalara kıyasla hem PSNR hem se SSIM ölçütlerı bağlamında önemli iyileştirmeler sağlamaktadır. Anahtar Kelimeler:Coupled K-SVD, Dalgacıklar, Tek Görüntü Süper Çözünürlük
Master of Science in Electrical and Electronic Engineering. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Engineering, Dept. of Electrical and Electronic Engineering, 2015. Supervisor: Prof. Dr. Hüseyin Özkaramanlı.
Keywords: Electrical and Electronic Engineering; Computer vision; Image processing - Digital techniques; Image Analysis; High resolution imaging - Image reconstruction; Coupled K-SVD; Wavelets; Single Image Super - Resolution